1998
DOI: 10.1002/(sici)1521-4141(199812)28:12<4062::aid-immu4062>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide regulates Th1 cell development through the inhibition of IL-12 synthesis by macrophages

Abstract: We have previously reported that mice lacking inducible nitric oxide synthase (NOS2) developed enhanced Th1 cell responses. We now investigated the mechanism by which NO modulates Th1 cells differentiation. Peritoneal macrophages from NOS2-deficient mice infected with Leishmania major in vivo or stimulated with IFN-gamma or lipopolysaccharide (LPS) in vitro produced significantly higher levels of IL-12 than those from heterozygous or wild-type mice. A macrophage cell line, J774, produced significant amounts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
129
0
4

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 201 publications
(142 citation statements)
references
References 37 publications
9
129
0
4
Order By: Relevance
“…TNFα is known to be a key mediator of pathogenesis in a broad range of infectious and predominantly Th-mediated inflammatory diseases, possibly via macrophage induction of iNOS and thus NO synthesis. However, iNOS has also been shown to enhance induction of TNFα synthesis [23] , contributing to local tissue destruction during the chronic inflammation that is one of the direct consequences of inflammatory processes. A previous study found a positive correlation between iNOS activity levels and disease severity in patients with ulcerative colitis, but this association is less clear in Crohn's disease [24] .…”
Section: Discussionmentioning
confidence: 99%
“…TNFα is known to be a key mediator of pathogenesis in a broad range of infectious and predominantly Th-mediated inflammatory diseases, possibly via macrophage induction of iNOS and thus NO synthesis. However, iNOS has also been shown to enhance induction of TNFα synthesis [23] , contributing to local tissue destruction during the chronic inflammation that is one of the direct consequences of inflammatory processes. A previous study found a positive correlation between iNOS activity levels and disease severity in patients with ulcerative colitis, but this association is less clear in Crohn's disease [24] .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying these effects are not clear. Involvement of NK cells (1) or macrophages (28), or direct activity of NO on T cells (29), are the recently suggested explanations. In the present study, NK cell functions, e.g., cytotoxic activity and production of IFN-␥, are not altered in the absence of NOS2 in the current model.…”
Section: Discussionmentioning
confidence: 99%
“…The production by macrophages of a variety immunomodulatory cytokines (e.g., IL-12, IL-1) can be inhibited by NO (Huang et al 1998, Obermeier et al 1999. Interestingly, NO can also modulate the actions of macrophage-derived cytokines on target cells.…”
Section: Macrophagesmentioning
confidence: 99%